Surface modification of stainless steel powders for microfabrication - Vieira, M. T. (2008)
The current trend towards miniaturization has led to the increasing use of stainless steel powders as raw material in the manufacture small parts with complex shapes, e.g. medical devices. This paper focuses on the role of coated and uncoated low carbon stainless steel powders, having d50 = 7.3 [mu]m, normal particle size distribution and a shape factor of 1 on additive processes used in micromanufacturing, e.g. micro powder injection moulding ([mu]PIM). Surfaces were treated using a magnetron sputtering deposition apparatus equipped with a high frequency powder vibration and a continuous feed system. The results clearly show that the coated powders assume an "artichoke" morphology, which significantly increases the surface area. This combined with their nanocrystalline character leads to higher flowability than uncoated powders. However, no improvements have been observed concerning the critical powder volume concentration (CPVC) in feedstocks for [mu]PIM processing. In consolidation processes, the debinding temperatures can attain values higher than 500 °C. After debinding and sintering, the coating of steel powders can show lower carbon contamination in solid solution than uncoated ones. This result is very important particularly for powder microtechnology of low carbon stainless steel.